PENGARUH STRATEGI PEMASARAN (PROMOTION MIX) IKLAN TERHADAP PENINGKATAN PENGGUNA JASA LAYANAN PERIKLANAN DI PT RADIO INDAH ASRI SRAGEN - Putri, Mahesi Andani; Triyaningsih, Sri Lestari (Universitas Slamet Riyadi, 2013)
ABSTRACT The purpose of this study were to analyze the significance of the influence of advertising , sales promotion, personal selling and publicity partially to service users of advertising in PT Radio Indah Asri Sragen. Methods of research using survey methods, sampling techniques using simple random sampling that is a total of 30 respondents. Data analysis techniques used validity test, reliability test, the classical assumption test, multiple linear regression analysis, t test, F test and the coefficient of determination. From this analysis, the dominant variable effect on service users advertising is the advertising variable. T test: (1) advertising significantly influence the advertising service users; (2) Sales Promotion significantly influence the advertising service users; (3) Personal selling significantly influence the advertising service users; (4) Publicity significantly influence the advertising service users; (5) The results obtained coefficient of determination value of Adjusted R Square = 0,899 means that the note given by the influence of the independent variables, of the dependent variable is the advertising service users was 89,9% while the remaining 10,1% is influenced by other variables. Keywords: advertising, sales promotion, personal selling, publicity and advertising service users